THAI STATE, HEALTH DISCOURSES AND SUBALTERNITY AMONG MAGRANT WORKERS: LESSON LEARNED FROM THAILAND - Photikanit, Kammales; Sirasoonthorn, Patcharin; Aneksuk, Boonyasarit; Buddharaksa, Watcharabon (PEOPLE: International Journal of Social Sciences, 2018)
This article aims to analyze the subalternate condition among migrant workers in Thailand under Thailand government’s health policy during 2001 – 2016. The major objective of this research work is to critique and reveal the complication of socio – politics and Thai state’s health policies which affected migrant worker’s subalternity. The authors applied documentary research by adopting Gramscian approach which did not only focus on research methodology in scientific method such as statistical analysis or mathematical statistics, but the criticism approach was crucial. By using this approach, the critique of power and knowledge establishment in form of the order of things by using the critical policy perspectives had also been highlighted for analyzing the formation of Thai state’s health policy and its effects to subalternity among migrant workers in Thailand. The researchers found out that subalternity among migrant workers in Thailand was not a new scenario. Rather, it had been continually reproduced through various Thai state ideological apparatuses and Thai state’s health policy. On one hand, two major initiative thoughts of policy formation were reproduced to take and maintain Thai state’s hegemony and share benefits among their alliances. On the other hand, the subalternity also stigmatized those migrant workers, who were subconsciously considered as “the otherness”. The social exclusion had been highlighted as well as the condition of out of sight, out of mind which had also remained in Thai state’s heedfulness.